2015
DOI: 10.1021/acs.jpclett.5b01501
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and Characterization of a Single Hydrogen Molecule in a Continuously Tunable Nanocavity

Abstract: KEYWORDS: Nanocavity, nano-reactors, vibrational and rotational modes, scanning tunneling microscope, electronic density of states, van der Waals interaction. + These two authors contributed equally to this work.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
(63 reference statements)
4
24
0
Order By: Relevance
“…When the distance between the second-topmost surface layers of the Au-H 2 -Au junction is set to 22.0Å (the distance between the electrodes is arbitrary, since in real experiments, it is set by the break junction setup) [38][39][40][41][42], the equilibrium distance between the electrodes' topmost layers is optimized to 17.82Å, and the conductance is 0.74G 0 , in agreement with Ref. [43].…”
Section: Resultssupporting
confidence: 70%
“…When the distance between the second-topmost surface layers of the Au-H 2 -Au junction is set to 22.0Å (the distance between the electrodes is arbitrary, since in real experiments, it is set by the break junction setup) [38][39][40][41][42], the equilibrium distance between the electrodes' topmost layers is optimized to 17.82Å, and the conductance is 0.74G 0 , in agreement with Ref. [43].…”
Section: Resultssupporting
confidence: 70%
“…The depth appears to increase rather linearly with tip charge such that energies in the range of a few hundred meV are attainable. We thus observe already in this simple system a trapping of the molecule that has been stated by Wang et al [7] for nanocavities built by an atomic environment at a surface. Additionally, the trapped H 2 in this potential well, where the tip distance can be mapped onto the tip bias, experiences a bias-dependent varying force.…”
Section: Ground Statesupporting
confidence: 79%
“…This implies that we must dispense here with charge neutrality, which would characterize normal environments of a H 2 molecule, such as in a crystal or a liquid. Oppositely charged tips are also of interest because of the voltage drop and the electric current characteristic in the H 2 bridge experiments [7][8][9][10][11][12][13]. This will be pursued in later work.…”
Section: A Hydrogen Molecule Between Two Tipsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was reported that the enhanced resolution also occurs at a relatively large tip to surface distance where the Pauli repulsion is negligible [11]. A theoretical study has proposed that the enhanced resolution results from the change of the adsorption state of the trapped H 2 in the junction [12]. Hydrogen molecular junctions (HMJs) have also been studied as a simple model of molecular junctions, and conductivity and mechanical properties of the HMJs have been measured using mechanical break junction [13][14][15][16][17], STM [18][19][20], and AFM experiments [21].…”
mentioning
confidence: 99%